ANALISIS KEPADATAN MAKROZOOBENTOS PADA FASE BULAN BERBEDA DI LAMUN, PULAU PANGGANG, KEPULAUAN SERIBU JAKARTA - Iswandi Wahab; Hawis Madduppa; Mujizat Kawaroe; Nurafni Nurafni (Jurnal Teknologi Perikanan dan Kelautan, 2019)
Seagrass ecosystems are inhabited by many species of benthic invertebrates, demersal and pelagic organisms that reside or stay temporarily in seagrass ecosystems. This research aimed to analyze the density of the macrozoobenthos in two different moon phases and to seek the contribution of each macrozoobenthic species in each research stations at seagrass beds. Sampling of the macrozonthic organisms was taken in three research stations of Panggang Island (west, east, and south) by using a 1 x 1 m of quadratic transect and a sediment corer with 10 cm in diameter. The data analysis statistically analysis data was carried out by finding out the similarity percentage of the species contribution using SIMPER test. Results of this research indicate that the discovered macrozoobenthos for two phases of moon are varied in each station. The total found macrozoobenthos during two moon phases are 28 and 11 species in the west station, 24 and 20 species in the east station, and 18 and 24 species in the south station, respectively. In the three stations, the two highest and the lowest species density of macrozoobenthos during the two moon phases namely are Cerithium salebrosum (283 ind/m2) and Cerithium punctatum (169 ind/m2); and Geotrochus multicarinatum (7 ind/m2). Moreover, the most contributor species of macrozobenthos in the seagrass habitat of the entire stations is Cerithium salebrosum.